Mass production and field evaluation of Beauveria brongniartii (Saccardo) against Brahmina coriacea (Hope) whitegrubs in potato - soni, saurbh; Mehta, Pawan Kumar; Chandel, Ravinder Singh; Kalia, Monika (Potato Journal, 2017)
An attempt was made to control the whitegrub, Brahmina coriacea using local isolates viz. KH I and KH II of entomopathogenic fungi, Beauveria brongniartii at field level in high hills of Himachal Pradesh. For mass multiplication of B. brongniartii, four grain media viz. cowpea, maize, sorghum and oat were tested and evaluated to select the suitable substrate for growth and mass multiplication. Cowpea was found to be best substrate showing maximum vertical growth of fungus (6.60-6.97 cm) in test tubes. Spore count was maximum (2.30Ã—107 conidia/ml) in KH I isolate on cowpea. The fungus was multiplied in polypropylene bags on crushed, overnight presoaked cowpea grains. Within 21 days, the grains were covered by good growth of fungus and were used for field application. Under field conditions, double application of B. brongniartii (KH I) @ 1014 spores/ha was found effective. There was 44.85 per cent reduction in tuber damage on weight basis as compared with the control at the time of harvesting, whereas 33.99 per cent reduction in the grub population was observed in the treated plot as compared to untreated check.Â